Private Brand Development Strategy in the Jakarta Retail Sector in 2025: Digital Adaptation and Sustainability Amidst the Global Recession - Oktrainal, Rijalul Fikri; Ariyani, Nafiah (Lentera Ilmu Nusantara, 2025)
This study aims to examine the strategy for developing personal brands in the retail sector in Jakarta in 2025, implemented amidst a global economic recession that impacts consumer behavior and market dynamics. Adopting a mixed methods approach, the study analyzes quantitative data from the Central Bureau of Statistics (BPS) and consumer survey results, combining these with qualitative analysis from case studies and related literature. The results indicate that successful personal brand development depends on the ability to authentically integrate digital adaptations and transparently implement sustainability values. The use of social media, live shopping, and collaboration with micro-influencers significantly contribute to building emotional connections and increasing consumer engagement. Meanwhile, sustainability practices and supply chain transparency are becoming competitive advantages that attract increasingly socially and environmentally conscious consumers. An emphasis on value-based marketing, which emphasizes product quality and social impact, has been shown to increase customer loyalty and drive adaptive and sustainable business growth in challenging economic conditions.